P123 Impulse oscillometry (IOS) indices in severe asthma and healthy controls after deep breath manoeuvres and bronchodilator administration. (16th November 2010) - Umar, I; Desai, D; Corkill, S; Shelley, M; Singapuri, A; Brightling, C; Siddiqui, S
Abstract : Introduction: Impulse oscillometry is a non-invasive method used to measure airway impedance. There is increasing interest in utilising frequency dependence of airway resistance/reactance to study small airways disease in asthma. We examined frequency dependant behaviour in severe asthma and the response to deep inspiration and bronchodilators. Methods: 27 healthy controls (C) (Mean (sem) age; 48.4 (2.2), Sex M:F; 9:18, post-bronchodilator FEV1 % predicted; 108.2 (2.8)%) and 66 GINA stage 4–5 severe asthmatics (A) (Mean (Sem) age; 54.1 (1.4), Sex M:F; 31:35, post-bronchodilator FEV1% predicted; 81.02(2.7)%), were recruited from Glenfield Hospital, UK. Impulse oscillometry (IOS) was performed at 5–35 Hz, with impulses triggered every 0.2 s for 150 s, at (1) baseline (base) (2) immediately after five deep breaths (TLC-RV) (pdb) (3) 15 min after 400 mcg inhaled salbutamol (pbd). Markers of total (R5) and large airway (R20) resistance, and frequency dependant behaviour of resistance (R5-R20) and reactance area (AX) were evaluated.Triplicate measurements of 150 s were performed in 18 randomly selected asthmatics from our cohort to assess repeatability. Results: Impedence measurements were highly repeatable (an intra-class correlation of 0.9) in the triplicate series. We observed asignificant increase in frequency dependence of both resistance (R5-R20) and reactance (AX) after deep inspiration in asthma, but not in healthy controls, which was reversed by the use of a bronchodilator (Abstract P123 Figures 1A–D ). In addition R20 increased in both severe asthma and healthy controls after deep inspiration. Conclusions: Deep inspiration significantly increased frequency dependence of resistance and reactance in severe asthma suggesting that the small airways may be related to the aberrant deep inspiratory response in severe asthma.